Self-Efficacy as a Mediator between Financial Autonomy and Educational Support in Enhancing University Students’ Motivation - Jamal Adri; Sandi Sandi; Andi Emil Salim (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2025)
This study aims to examine the influence of entrepreneurship education on student motivation through self-efficacy, as well as the impact of financial autonomy on student motivation with self-efficacy as a mediating variable. The research was conducted at the Faculty of Economics and Business, Universitas Negeri Makassar, involving students participating in entrepreneurship education programs. A quantitative approach was employed using a descriptive-explanatory research design. Data was collected through structured questionnaires distributed to 96 randomly selected respondents, and analyzed using path analysis techniques. The findings reveal that entrepreneurship education has a significant and positive influence on student motivation, mediated by self-efficacy. This indicates that quality entrepreneurship education enhances students’ self-confidence, which in turn boosts their motivation to succeed academically and entrepreneurially. Furthermore, financial autonomy also shows a positive effect on student motivation through the enhancement of self-efficacy, suggesting that students with greater financial independence tend to exhibit higher self-belief and stronger motivation to achieve both academic and entrepreneurial goals. These results highlight the essential role of self-efficacy as a bridge connecting educational and financial support to student motivation in higher education contexts.